Роман «Тигролови» І. Багряного: спроба корекції української національної ментальності - Кудря, Г.М. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2006)
Among the peculiarities of national mentality which are changed in the novel "The Hunters and the Hunted" by I. Bagriany the reasearcher distinguishes such features as individualism, cordocentrism (Greek cardia - the heart and Latin centrum - the centre) and antaeism (from the Antaeus, a giant in Greek mythology).
Keywords: Багряний; Тигролови; українська ментальність